ANTIBACTERIAL ACTIVITY OF DIFFERENT EXTRACTS OF BLACK MUSSEL (MYTILUS GALLOPROVINCIALIS) FROM THE BLACK SEA, BULGARIA - Gabriela Tsankova; Tatina Todorova; Neli Ermenlieva; Albena Merdzhanova; Veselina Panayotova; Diana Dobreva; Katya Peytcheva (Peytchinski Publishing, 2021)
Background: Over the past decade, there has been a growing interest in sea bivalves, which are an inexpensive and easily accessible source of high-quality proteins, lipids and secondary metabolites with antimicrobial and anti-fungal potential. Farmed Black Sea mussel (M. galloprovincialis) are promising objects for the study of their antimicrobial potential. Purpose: The aim of this work is to determine the antibacterial activity of different extracts from the Black Sea mussel Mytilus galloprovincialis tissues by using the disc diffusion method with cultures of Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae. Material/Methods: Extraction of mussel tissues was done with different solvents: ethyl acetate (100%), methanol (100%), glycerol:water (50%, 1:1 v/v), ethanol (50%), acetone (70%), hot water. Antimicrobial activities of these extracts from Mytilus galloprovincialis was assessed by the disc-diffusion method. Results: Testing antibacterial activity of black mussels revealed that ethyl acetate extract showed the highest activity against Еscherichia coli (13 mm) and Klebsiella pneumoniae (11 mm) and no activity against Staphilococcus aureus. The glycerol: water extract showed growth inhibition effect against Staphylococcus aureus (11 mm) and Escherichia coli (10 mm), but no effect against Klebsiella pneumoniae. Conclusions: The preliminary information presented in this study showed that the Black Sea farmed mussel could be an interesting source of antibacterial compounds. The glycerol-water extracts of Mytilus galloprovincialis had low antimicrobial activities against Staphylococcus aureus and more important against Escherichia coli.